Sterically demanding pyridine-quinoline anchoring ligands as building blocks for copper(i)-based dye-sensitized solar cell (DSSC) complexes. Issue 39 (16th September 2022) - Peppas, Anastasios; Sokalis, Demetrios; Perganti, Dorothea; Schnakenburg, Gregor; Falaras, Polycarpos; Philippopoulos, Athanassios I.
Abstract : A nanocrystalline TiO2 dye-sensitized solar cell device consisting of dye 2 and fabricated with commercially available materials reaches a conversion efficiency of η = 1.20%. Dye 2 is a low-cost and easily prepared copper(i ) molecular sensitizer. Abstract : The Pfitzinger condensation reaction was employed to synthesise N^N sterically demanding ligands bearing carboxylic acid anchoring groups, namely 2, 2′-pyridyl-quinoline-4-carboxylic acid (pqca ), 6′-methyl-2, 2′-pyridyl-quinoline-4-carboxylic acid (6′-Mepqca ), 8-methyl-2, 2′-pyridyl-quinoline-4-carboxylic acid (8-Mepqca ) and 8, 6′-dimethyl-2, 2′-pyridyl-quinoline-4-carboxylic acid (8, 6′-Me 2 pqca ). Preparation of the methyl ester analogues 6′-Mepqcame, 8-Mepqcame and 8, 6′-Me 2 pqcame is also described. All ligands were fully characterised including the X-ray structures of pqca, 6′-Mepqca and 8-Mepqca . We also describe the synthesis and characterisation of seven homoleptic copper(i ) complexes of the formula [Cu(N^N)2 ][PF6 ] (N^N = pqca (1 ), 6′-Mepqca (2 ), 8-Mepqca (3 ), 8, 6′-Me2 pqca (4 ), 6′-Mepqcame (6 ), 8-Mepqcame (7 ) and 8, 6′-Me2 pqcame (8 )). Characterisation of the copper(i ) complexes includes FT-IR, elemental analyses, multinuclear NMR spectroscopy, UV-vis spectroscopy, cyclic voltammetry, and a single-crystal X-ray diffraction study. The molecular structures of 1 ·DMSO, 2{2 ·Me2 CO·0.5H2 O}, 4, 6 ·CHCl3 ·0.13H2 O, 2{7 ·C 5 H12 }·CHCl3 and 8 have been determined, revealing that these complexes adopt a distorted tetrahedral geometry. These are the first crystallographically characterised examples of copper(i )-based coordination compounds incorporating the above mentioned N^N pyridyl-quinoline ligands. In solution, the new complexes are purple to red colored, while 2 displayed excellent stability in acetone at ambient temperature over a month. The absorption spectra of 1–8 display a main broad MLCT band with values of λ max at ∼530 nm and ε values ranging from 1800 to approximately 10 000 dm 3 mol −1 cm −1 . The photovoltaic performance of the prepared compounds was evaluated on mesoporous nanocrystalline TiO2 dye-sensitized solar cells (DSSCs), and compared with that of the [Cu(dmdcbpy)2 ][PF6 ] dye (dmdcbpy = 6, 6′-dimethyl-2, 2′-bipyridine-4, 4′-dicarboxylic acid) (5 ), that has been used as standard, under the same experimental conditions. From a combination of electrochemical and absorption spectroscopy experiments, the MLCT energy levels of 2 are appropriate for electron injection onto the titania conduction band. Upon optimisation of the semiconductor's architecture, 2 proved to be the most efficient dye, reaching a conversion efficiency of η = 1.20%, which is slightly higher than that of 5 ( η = 1.05%), mainly attributed to higher V oc values.